Cooking energy pattern in rural India and their institutional implications for energy-shed micro planning - Sekhar, R.C
The paper analyses the consumption pattern of cooking energy in 221 households, in 13 villages spread throughout the country, using a detailed questionnaire having 160 items. It comes to the conclusion that cost-effective innovations unaided by rural energy planners and appropriate technologies may have helped the rural population coping with the cooking energy problems. Secondly, it uses multiple regression statistical analysis to show that energy patterns have greater homogeneity across economic classes within the same village than within economic classes across villages. Lastly it shows the desirability of leaving cooking energy planning entirely to people's initiative, thus covering 68
Keywords: Rural Development; IRDP; Energy Resources - India